2019
DOI: 10.1038/s41388-018-0659-4
|View full text |Cite
|
Sign up to set email alerts
|

Histoepigenetic analysis of HPV- and tobacco-associated head and neck cancer identifies both subtype-specific and common therapeutic targets despite divergent microenvironments

Abstract: Although head and neck squamous cell carcinoma (HNSCC) has in the past been largely associated with tobacco use, human papillomavirus (HPV+) oropharynx cancer has in recent years emerged as the fastest growing type of HNSCC. Patients with HPV+ HNSCC have a better prognosis; however, the 5-year survival for both HPV+ and HPV− subtypes with recurrent or metastatic disease is poor. To gain insights into the tumor microenvironments of both HNSCC subtypes and identify potential therapeutic targets, we performed epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…Generally, smoking is associated with HPV negative, while non-smoking tends to be HPV positive in relation to HNSCC (oral squamous cell carcinoma mainly) [48]. Previous studies have found that the presence of virus-related antigen provides an advantage; patients who are HPV positive are more likely to benefit from anti-PD-1/PD-L1 therapy than patients with negative ones [12]. In two RCTs we included, although the correspondence between smoking status and HPV infection was consistent, the study by Ferris et al [4] supposed the previous ones, while the study by Cohen et al [8] was the opposite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, smoking is associated with HPV negative, while non-smoking tends to be HPV positive in relation to HNSCC (oral squamous cell carcinoma mainly) [48]. Previous studies have found that the presence of virus-related antigen provides an advantage; patients who are HPV positive are more likely to benefit from anti-PD-1/PD-L1 therapy than patients with negative ones [12]. In two RCTs we included, although the correspondence between smoking status and HPV infection was consistent, the study by Ferris et al [4] supposed the previous ones, while the study by Cohen et al [8] was the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…In melanomas, Ribas et al [11] found that intratumoral injection of an oncolytic virus will enhance the immune recognition of cancer, resulting in a high response rate in patients with advanced disease. In squamous cell carcinoma of head and neck (HNSCC), higher expression of the immunotherapy target PD-1 in HPV+ immune cells compared to HPV− cells was observed, suggesting that HPV+ patients may preferentially benefit from anti-PD-1 therapy [12]. In NSCLC, the benefit of anti-PD-1/PD-L1 therapy was even correlated with intestinal flora [13].…”
Section: Introductionmentioning
confidence: 99%
“…39 It has been shown that Ror2 is expressed highly in lung adenocarcinoma cells harboring p53 loss-of-function mutations 40 and in human papillomavirus (HPV)-positive head and neck squamous cell carcinoma, where HPV oncogenic protein E7 represses Rb. 41 Interestingly, multiple putative E2F binding sites are found within the nucleotide sequences at regions approximately 200 bp upstream of the Ror2 genes, that are conserved highly between mouse and human. Therefore, it can be envisaged that E2F1 might also be involved in induced expression of Ror2 in highly proliferative cancer cells with p53 mutations or infected with HPV.…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient PD-1 + T cells subset represented the previous activation state of T cells against tumors, which could be reactivated by PD-1/PD-L1 blockade (57). Additionally, a histoepigenetic analysis showed that HPV-positive HNSCC had a higher level of both infiltrated CD8 + T and B cells in the tumors as well as higher PD-1 expression in immune cells, which may lead to a better response rate by PD-1 targeted therapy (63).…”
Section: Biological Significance and Prognosis Value Of Pd-1/pd-l1 Axmentioning
confidence: 99%